POTENTIAL CHINESE DEBT TRAP IN INFRASTRUCTURE DEVELOPMENT (CASE STUDY OF THE JAKARTA-BANDUNG HIGH-SPEED RAILWAY PROJECT) - Afifah , Nadia Renata Nur; Badaruddin , Muhammad (Indonesian Association for International Relations, 2024)
This study aims to determine the potential that will occur from Chinese loans in the Jakarta-Bandung High-Speed Train infrastructure project. This research uses qualitative methods with a case study approach. This paper discusses the Jakarta-Bandung High-Speed Train project with an analysis of debt trap theory through the analysis of four main aspects that are categorized, namely: first, financial transactions occur in the form of Chinese loans with Indonesia. Second, Indonesia does not have the potential to repay its debt burden to China based on the country's foreign exchange reserves, Indonesia's GDP level against projected debt returns to China, and China's debt rating in Indonesia. Third, the construction of KCJB took place in the period 2013-2023. Based on research and analysis that has been done, it is obtained that the Jakarta-Bandung High-Speed Train project has the potential for a debt trap from China because it meets all four aspects of the debt trap theory